A mulher idosa e a criminalidade: uma compreensão na perspectiva bioecológica do desenvolvimento humano. - Vilela, Daniely da Silva Dias (2021)
This dissertation main objective is to comprehend what leads some elderly women, after a lifetime without involvement with the justice system, ended up committing a crime. Specifically, our purpose was: 1) to indicate and contextualize the Human Development Theory using ideas originated on a the bioecology perspective; 2) know the context that contributed to elderly women to incur the crime; 3) to analyze the factors that influence some aging and elderly people in commit crimes. This research is qualitative, transversal, exploratory and descriptive. The sample consisted of five elderly women who are serving time in correctional institutions in the State of Pernambuco. The data collection instruments consisted of a bio sociodemographic questionnaire and a semi-structured interview. Data analysis was conducted using the Human Development Theory in the Bioecological perspective, which proposes the analysis of the relationship between the four elements of the PPCT model (person, process, context and time) to understand human phenomena. The results show that the participants are between 60 and 71 years old, an education level incomplete elementary education, are divorced or single, retired or pensioners, with income of one minimum wage, and have between five and three children, six and four grandchildren, one to three great-grandchildren and are visited by their daughters. The most prevalent diseases are hypertension, memory problems, diabetes, back problems and labyrinthitis. They were condemned predominantly for drug trafficking, followed by attempted murder and fraud. Penalties ranged from 8 to 14 years in prison. With regard to the motivations for crime, it appears that the bioecological contexts that involve the lives of these people acts as facilitators to entry into the criminality. In short, prisons for incarcerated elderly women can be understood as a family experience. As a rule, they are affected by the deprivations in life, characteristic that affect those who live on the suburbs, and many of them see drug trafficking as a possibility for a better life, both for them and for their family. Therefore, personality characteristics; life's history; small pensions and, the lack of guaranteed means of survival; family ties, more precisely the influence of children and grandchildren contributed decisively to their entry into crime. Therefore, it is hoped that the results obtained can inform the work of professionals interested in organizing projects to promote the life quality of elderly people at risk of involvement with crime or already involved, such as those who are incarcerated. In addition, it is expected to collaborate to minimize the impacts of the increase in the number of the elderly in prisons by encouraging policies and actions to prevent their involvement with crime, in the Northeast region of Brazil, especially in the State of Pernambuco.